ESP bermuatan Competency-based Instruction Approach pada Mahasiswa Politeknik Palu Program Studi Hasil Laut - Hendriyani; Yusniarti Runggo (Universitas Tadulako, 2021)
This is classroom action research aims to increase learning outcomes and competence of students through the implementation of ESP with Competency-based Instruction Approach. The research was conducted at Politeknik Palu with 30 students as the subjects of the research. The data were gathered through observation and competency test. The results reveal that 16 students or 53.3% succeeded in cycle 1. Then, it increased to 25 students or 83.3% in cycle 2. In conclusion, the implementation of ESP with Competency-based Instruction Approach can improve students’ learning outcomes and competencies.